2021
DOI: 10.1002/admt.202100528
|View full text |Cite
|
Sign up to set email alerts
|

High‐Strength Flexible Membrane with Rational Pore Architecture as a Selective Radiator for High‐Efficiency Daytime Radiative Cooling

Abstract: radiative cooling requires a radiator with spectral selectivity, which refers to high absorptivity/emittance only in the atmospheric window (8-13 µm) and an extremely high solar reflectance (0.3-2.5 µm). [2] Traditional solutions combine a shielding layer and a radiative layer [3] or a radiative layer and a reflective metal layer. [2b,4] However, conventional materials and their combinations have a limited cooling effect because of their inability to satisfy the stringent requirements for selectivity. In 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Shorter film formation times would therefore be desirable to minimize this effect. A promising spray-phase-separation strategy was applied by Wang et al , 61 in which the slurry is atomized into small droplets during the spraying process, and phase separation occurs thereon (Fig. 3d).…”
Section: Development Of Single-polymer Radiative Cooling Materialsmentioning
confidence: 99%
“…Shorter film formation times would therefore be desirable to minimize this effect. A promising spray-phase-separation strategy was applied by Wang et al , 61 in which the slurry is atomized into small droplets during the spraying process, and phase separation occurs thereon (Fig. 3d).…”
Section: Development Of Single-polymer Radiative Cooling Materialsmentioning
confidence: 99%
“…13,19 Thus, based on the biological inspirations, we realized that we could capture the novelty of this work by reproducing the dual functionalities of the butterfly species by mimicking the wing scale nanostructures and further enhancing the radiative cooling and structural cooling capabilities through experimental optimization. It was reported that the porous structure contributes to the radiative cooling enhancement, [20][21][22] but these studies rely on phase separation methods to fabricate a porous film, which is not a precise method to control the pore size and thereby reproduce the porous structure of the butterfly wing scales. In contrast, the solution process to create an inverse opal structure offers a facile fabrication platform to precisely control the pore size and spatially distribute the pores because the size of the sacrificial template directly corresponds to the pore size of the inverse opal structure as much previous literature about inverse opal structures has demonstrated for other applications.…”
Section: Introductionmentioning
confidence: 99%
“…Daytime radiative cooling materials are designed to satisfy specific spectral selectivity, which means high solar reflectance in the visible–near-infrared wavelength range (0.3–2.5 μm) and high emissivity in the atmospheric transparency window (8–13 μm) . Photonic crystals, , multilayer radiators, , particles embedded in composite materials, hierarchically porous structure materials, and other types of radiators have been designed, which have promising cooling applications in buildings, solar cells, wearable clothes, and water condensation …”
Section: Introductionmentioning
confidence: 99%